Cross-Cultural Adaptation and Validation of the Neck Disability Index to European Portuguese Language. Issue 2 (15th January 2015) - Cruz, Eduardo Brazete; Fernandes, Rita; Carnide, Filomena; Domingues, Lúcia; Pereira, Marta; Duarte, Susana
<x xml:space="preserve">Abstract</x> Study Design. Cross-cultural adaptation and psychometric testing. Objective. To complete the cultural adaptation of the European Portuguese version of the neck disability index (NDI-PT) and to investigate its reliability and validity in patients with chronic neck pain (CNP). Summary of Background Data. The NDI is the most widely used instrument for self-reporting of disability due to neck pain. Although the NDI has demonstrated both good reliability and validity, a recent systematic review called attention for the poor methodological quality of the translation processes and psychometric studies. Methods. The NDI-PT was first piloted in a sample of 40 patients with CNP. Then, 113 patients with CNP completed the numeric pain rating scale and twice the NPI-PT with an interval of 4 to 7 days. Factor structure of the NDI was explored through principal component factor analysis. The internal consistency was estimated using the Cronbach α coefficient. Reliability was determined by repeatability using intraclass correlation coefficient (2, 1) for the total sample and for the subsample of participants who remained stable in CNP status between the initial and follow-up assessment based upon the global rating of change scale, and agreement using the concept of "limits of agreement." Construct validity was assessed with correlations between the NDI-PT and the numeric pain rating scale for convergent validity, using Pearson correlation analysis. Results. Exploratory factor analysis revealed the existence of 1 major factor that explained 54.7% of the variance. Test-retest reliability was 0.9 and internal consistency was 0.95. No systematic trend was observed in the Bland and Altman method. The NDI-PT showed a good correlation with pain intensity (r = 0.525, P < 0.01). Conclusion. The NDI-PT demonstrated excellent reliability and good construct validity and it may be useful for assessing functional status of Portuguese-speaking patients with CNP. Level of Evidence: N/A